A Low Dose of Dietary Quercetin Fails to Protect against the Development of an Obese Phenotype in Mice. - Reilly T Enos; Kandy T Velázquez; Meredith S Carson; Jamie L McClellan; Prakash Nagarkatti; Mitzi Nagarkatti; J Mark Davis; E Angela Murphy (PLoS ONE, 2016)
The purpose of this study was to examine the effect of a 40% high-fat diet (HFD) supplemented with a dietary attainable level of quercetin (0.02%) on body composition, adipose tissue (AT) inflammation, Non-Alcoholic Fatty-Liver Disease (NAFLD), and metabolic outcomes. Diets were administered for 16 weeks to C57BL/6J mice (n = 10/group) beginning at 4 weeks of age. Body composition and fasting blood glucose, insulin, and total cholesterol concentrations were examined intermittently. AT and liver mRNA expression (RT-PCR) of inflammatory mediators (F4/80, CD206 (AT only), CD11c (AT only) TLR-2 (AT only), TLR-4 (AT only), MCP-1, TNF-α, IL-6 (AT only), and IL-10 (AT only)) were measured along with activation of NFκB-p65, and JNK (western blot). Hepatic lipid accumulation, gene expression (RT-PCR) of hepatic metabolic markers (ACAC1, SREBP-1, PPAR-γ), protein content of Endoplasmic Reticulum (ER) Stress markers (BiP, phosphorylated and total EIF2α, phosphorylated and total IRE1α, CHOP), and hepatic oxidative capacity were assessed (western blot). Quercetin administration had no effect at mitigating increases in visceral AT, AT inflammation, hepatic steatosis, ER Stress, decrements in hepatic oxidative capacity, or the development of insulin resistance and hypercholesterolemia. In conclusion, 0.02% quercetin supplementation is not an effective therapy for attenuating HFD-induced obesity development. It is likely that a higher dose of quercetin supplementation is needed to elicit favorable outcomes in obesity.